An Appeal for Autonomy, Access, and Accountability in Family Court Reform Efforts. (October 2014) - Davis, Gabrielle; Ver Steegh, Nancy; Frederick, Loretta
<x xml:space="preserve">Abstract</x> An array of dispute resolution alternatives should be available to families who elect to use them. We suggest a system where parties maintain unhindered access to traditional courts but are able to knowingly and voluntarily opt into dispute resolution processes that are delivered in a fair, affordable, and accountable manner. We support provision of community‐based and private‐sector services to the extent that court funding and access is not diminished. Key Points for the Family Court Community Choices about participation in dispute resolution processes should be party driven. Parties should receive complete and accurate information about available dispute resolution processes and have access to confidential legal advice. Dispute resolution processes should be fair, affordable, competently provided, and accountable. Parties should have open access to traditional court processes.